if a+2b+c=0 then show that a3+8b3+c3=6abc
ansariabuzar3662:
tricky question
Answers
Answered by
6
Step-by-step explanation:
given a+2b+c=0
(a + 2b + c)³ = 0
=> (a + 2b)³ + 3(a + 2b)²c + 3(a + 2b)c² + c³=0
=> (a³ + 6a²b + 12ab² + 8b³) + 3c(a + 2b)(a + 2b + c) + c³= 0
= (a³ + 8b³ + c³) + 6ab(a + 2b) = 0
=> a³ + 8b³ + c³ - 6abc = 0
a+2b = -c (given)
=> a³ + 8b³ + c³ = 6abc
Answered by
11
Answer:
a + 2b + c = 0
a + 2b = - c
(a + 2b)³ = (-c)³
a³ + 8b³ + 3(a*2b) (a+2b) = -c³
a³ + 8b³ + 6ab(-c) = -c³
a³ + 8b³ - 6abc = -c³
a³ + 8b³ + c³ = 6abc
Hence proved
Expansion:
An algebraic expression multiplied by itself ( any Number of times) when expressed as a polynomial is called an Expansion.
In fact the term 'expansion' is used for the process of such multiplication.
A corollary is a result or relation that follows from another result or relation that is known.
Similar questions